Oxidative stress in patients with obstructive sleep apnoea syndrome - PASSALI, D. (Acta Otorhinolaryngol Ital, 2015)
Obstructive sleep apnoea syndrome (OSAS) is a disorder that leads to metabolic abnormalities and increased cardiovascular risk. The aim of this study was to identify early laboratory markers of cardiovascular disease through analysis of oxidative stress in normal subjects and patients with OSAS. A prospective study was designed to compare outcomes of oxidative stress laboratory tests in 20 adult patients with OSAS and a control group of 20 normal subjects. Laboratory techniques for detecting and quantifying free radical damage must be targeted to assess the pro-oxidant component and the antioxidant in order to obtain an overall picture of oxidative balance. No statistical differences in age, sex distribution, or BMI were found between the two groups (p>0.05). There were significant differences in the apnoea/hypopnoea index (AHI) between OSAS patients and the control group (p<0.05). Statistically significant differences in isoprostane, advanced oxidation protein products (AOPP) and non-protein bound iron (NPBI) levels were found between the study and control groups. No significant difference in the levels of thiol biomarkers was found between the two groups. The main finding of the present study was increased production of oxidative stress biomarkers in OSAS patients. The major difference between thiols and other oxidative stress biomarkers is that thiols are antioxidants, while the others are expressions of oxidative damage. The findings of the present study indicate that biomarkers of oxidative stress in OSAS may be used as a marker of upper airway obstructive episodes due to mechanical trauma, as well as a marker of hypoxaemia causing local oropharyngeal inflammation.